Pain Management Knowledge and Pain Control: a Cross-Sectional Study among Cancer Patients - Kartika, Imelda Rahmayunia; Rezkiki, Fitrianola (Jurnal Ilmiah Ners Indonesia, 2025)
Cancer is one of the diseases that causes the most deaths in the world. Cancer patients experience several symptoms due to the disease and the treatment they are undergoing. One of the symptoms that often appears is pain. The experience of cancer patients in controlling and managing pain is an important thing for nurses to pay attention to. Cancer patients require knowledge of pain management to effectively control the pain. This research aims to see the relationship between knowledge of pain management and pain control in cancer patients. This study used a cross-sectional design with a sample of 90 cancer patients at Government Hospital at Bukittinggi. The instrument in this study uses an adapted questionnaire from the Nursing Outcomes Classification (NOC) to measure both variables. Data were analyzed using Pearson correlation. The results of this study obtained p-value 0.000 (α=0.005), where it can be said that there is a significant relationship between knowledge of pain management and pain control in cancer patients. This research showed that the higher the knowledge, the better the pain control for cancer patients. Cancer patients need a lot of support from both health workers and family as caregivers in caring for patients when experiencing pain. This research can be a guide to paying more attention to the pain felt by cancer patients. It is also hoped that more education regarding non-pharmacological pain management will be carried out to improve pain control and pain management in order to improve the quality of life among cancer patients. Further research may be conducted to carry out the study about the relationship between pain management and quality of life among cancer patients.